A review on carbon-based self-sensing cementitious composites. (30th December 2020) - Han, Jinsheng; Pan, Jinlong; Cai, Jingming; Li, Xiaopeng
Highlights: The applications of different carbon fillers in cementitious composites were studied. The factors affecting the cementitious composites preparation and application were discussed. The current conductive theories, equivalent circuit models and main applications were summarized. Abstract: Self-sensing cementitious composite is a kind of cementitious material which possesses both mechanical and sensing properties. The stress and strain state of the structure can be analyzed by monitoring its electrical resistivity. This paper discussed the preparation, theory research, and application of self-sensing cementitious composites made with carbon-based materials. The applications of different types of carbon conductive fillers in cementitious composites as well as the influence factor were also investigated. The factors include the fillers' dispersion, electrode arrangement and electrical resistivity measurement methods, curing age, moisture content and temperature, etc. The conductive theory, equivalent circuit model of the composites and the current application forms were summarized. The challenges were finally discussed in the development and application of the self-sensing cementitious composites.